The Role and Impact of Australian Refugee Policy in Asia-Pacific Region: From Australia-Cambodia Agreement to Rohingya Crisis - Afira, Muhammad Ridho Inzaghi Putra (Mandala: Jurnal Ilmu Hubungan Internasional, 2021)
The issues of refugees has been a regional challenges that block the potential of Australia''s role in the Asia-Pacific. This article aims to discuss how Australian refugee policy influences its role in the Asia-Pacific Region. Therefore, this article will examine the background of Australia''s foreign policy towards the Asia-Pacific region from a historical perspective, how Australia made its policy regarding refugees, and discuss some of the latest issues to illustrate how this policy affects Australia''s role in the Asia-Pacific, namely: the agreement with Cambodia (2014), the Manus Island crisis (2017) and Australia''s response to the Rohingya crisis (2017). The author argues that the dynamics of domestic politics in Australia affect Australia's policy towards refugees. In the final analysis, Australia has been trying to limit refugees due to the domestic fear in Australia towards refugees, which has an impact on Australian policy and its role in the Asia-Pacific region.